Enhanced memory effect via quantum confinement in 16nm InN nanoparticles embedded in ZnO charge trapping layer - ALEVLİ, MUSTAFA (AMER INST PHYSICS, 2014)
In this work, the fabrication of charge trapping memory cells with laser-synthesized indium-nitride nanoparticles (InN-NPs) embedded in ZnO charge trapping layer is demonstrated. Atomic layer deposited Al2O3 layers are used as tunnel and blocking oxides. The gate contacts are sputtered using a shadow mask which eliminates the need for any lithography steps. High frequency C-V-gate measurements show that a memory effect is observed, due to the charging of the InN-NPs. With a low operating voltage of 4V, the memory shows a noticeable threshold voltage (V-iota) shift of 2V, which indicates that InN-NPs act as charge trapping centers. Without InN-NPs, the observed memory hysteresis is negligible. At higher programming voltages of 10 V, a memory window of 5V is achieved and the V-iota shift direction indicates that electrons tunnel from channel to charge storage layer. (C) 2014 AIP Publishing LLC.
Keywords: LASER-ABLATION; SEMICONDUCTORS; NANOCRYSTALS; GENERATION; BLUE